Factors affecting code switching: A case study of an urban family in Petaling Jaya - Ching Hei Kuang (Journal of Modern Languages)
The multi linguistic and multi-racial environment of a country like Malaysia is not only rich in cultures, traditions and food, but also in the varieties of languages (including dialects) used among speakers of the country. This phenomenon of using a variety of languages (including dialects) to perform speech functions has been identified by studies as code switching although such studies do not mention dialects. A phenomenon most commonly found among bilingual or multilingual societies, code switching has become an important issue in the studies of language and language use among people, communities and societies. Described as being the "most creative aspect of bilingual speech" (Hoffman 1991), it has also been seen as a mark of 'linguistic decay" and "a sign of laziness" (ibid.)